Image Fusion by Shift Invariant Discrete Wavelet Transform for Remote Sensing Applications - Abdalrahman Qubaa (College of Education for Pure Sciences, 2021)
The fusion technique of the spectral bands captured by the sensors carried onboard satellites is one digital processing method for extracting information and detecting ground targets. Image fusion - also known as pan-sharpening-provides the necessary means to combine many images into a single composite image that is suitable in visual interpretation processes or in digital interpretation. The principal objective of this study is to find the best suitable algorithms for obtaining integrative information from several separate images in one combined image. Based on the above, a special software system was designed to implement and test the fusion methods used in remote sensing applications by selecting and applying a Shift Invariant Wavelet Transform (SIWT) method to the remote sensing images and then comparing with four other different image fusion algorithms. Two objective mathematical methods were also used to measure the amount of shared information obtained in the images resulting from the fusion, as well as using the visual and Near-Infrared images of the new Sentinel-2 European satellite for a part of Nineveh province as experimental images. The results showed a preference of the wavelet transform method over the other fusion methods for the remote sensing images.